COVID‐19 in the geriatric population. (26th August 2020) - Roy, Justin; Jain, Rohit; Golamari, Reshma; Vunnam, Rama; Sahu, Nitasa
Abstract : Objectives: The global COVID‐19 pandemic has caused rapid and monumental changes around the world. Older people, who already experience higher rates of social isolation and loneliness, are more susceptible to adverse effects as a result of the social distancing protocols enacted to slow the spread of COVID‐19. Based on prior outbreaks, we speculate the detrimental outcomes and offer solutions. Methods: Reviewing the literature on the detrimental effects of social isolation and loneliness and higher mortality in the older population. Utilizing psychological study outcomes from prior major outbreaks such as in SARS, Ebola, H1N1 influenza, and Middle East respiratory syndrome offer predictions and the susceptibility in the geriatric age group. Results: Organizations such as the WHO, Centers for Disease Control, and American Association of Retired Persons have put measures in place to provide networking on a local, regional, and national level. These efforts are designed to start mitigating such detrimental effects. A necessary follow‐up to this pandemic will be gathering data on unique populations such as the geriatric community, to better mitigate adverse outcomes given the certainty that COVID‐19 will not be the last global viral outbreak. Conclusions: The results of worsened social isolation and loneliness is associated with significantly increased morbidity and mortality in the geriatric population. Various solutions including virtual interactions with loved ones, engaging in physical activity, continuing any spiritual or religious prayers remotely, and community services to provide aid for the older population are all efforts to minimize social isolation and loneliness.